Pre-existing mental health disorders and pregnancy. Issue 5 (May 2022) - Schofield, Zena; Enye, Stephen; Kapoor, Dipanwita
Abstract: Mental health disorders are independent risk factors for adverse perinatal and neonatal outcomes. It is estimated that 20% of women may experience symptoms of mental health disorders during or following pregnancy. It is important that obstetricians recognize the presentation of these symptoms and follow pathways for managing these conditions. This article utilizes case vignettes to describe the epidemiology, role of the multi-disciplinary team, clinical presentation, and management of common perinatal mental health disorders both from the obstetric and psychiatric view point. Indications and duration of psychotropic medications including side effects are also discussed as well as safety in pregnancy and lactation.